Maximizing or Satisficing - Kapteyn, Arie; Wansbeek, Tom; Buyze, Jeannine (The Review of Economics and Statistics, 1979)
T HE hypothesis that maximization underlies human behaviour is perhaps the most widely accepted paradigm among economists. Particularly in the study of consumer behaviour, numerous models have been built upon the hypothesis of maximization. Reviews of these models can inter alia be found in Houthakker (1961), Brown and Deaton (1972) and Barten (1977). The testing of the maximization hypothesis (HM) in real life situations appears to be a complicated affair. The main problem is that HM can only be tested conditional upon other assumptions. An individual's function' is commonly measured via the individual's observed behaviour. We call that indirect measurement. But the relationship between an individual' s and his behaviour is based on HM itself. Hence, having measured functions via HM it becomes difficult to use the measured to test HM. Therefore, testing HM mostly reduces to testing certain restrictions which have to be satisfied by parameters in a system of demand equations. However, testing these restrictions is not without problems, as testing a certain restriction has to take place conditional upon the validity of other restrictions.2 As far as testing has been carried out, results are not very encouraging (cf. Barten, 1977; Wales and Woodland, 1976). But, since many additional assumptions are involved,3 no firm conclusions can be drawn from these negative outcomes. Given these problems, several paths are open to the student of consumer behaviour. First he may want to dispense with the concept altogether and only hypothesize certain consistency properties of individual choices. This approach was taken by Samuelson (1938). If, however, the assumptions on individual preferences are made sufficiently strong, especially if one adopts the strong axiom of revealed preference, their implications for behaviour are equivalent to the restrictions derived from HM (cf. Houthakker, 1950; Stigum, 1973). Hence, testing the restrictions implied by the strong axiom of revealed preference is equivalent to testing HM. Empirical work in this area (cf. Koo, 1963; Mossin 1972) suggests that for everyday commodities (mainly food) most purchases of individual families are not inconsistent with the strong axiom of revealed preference theory. However, in many cases purchases are such that neither consistency nor inconsistency can be assessed (cf. Koo, 1963). Koo (1974) states that '6with few exceptions, almost all families made at least some inconsistent choices (p. 174). He finds that inconsistencies do not arise very often if purchases are in the neighbourhood of past experience. For less routine-like purchases inconsistencies are more likely to occur.4 Parenthetically, it may be mentioned that aggregate demand functions have a tendency to be in agreement with the strong axiom of reReceived for publication November 15, 1977. Revision accepted for publication November 16, 1978. * University of Southern California, Leyden University and Leyden University, respectively. The research reported in the paper is supported by grants from the Netherlands Organisation for the Advancement of Pure Research (ZWO) and the Dutch Ministry of Cultural Affairs, Recreation and Social Welfare. At the time of writing Arie Kapteyn was successively a fellow of the Netherlands Institute for Advanced Study in the Humanities and Social Sciences (NIAS) and at Leyden University. The empirical results are based on a survey, designed by B. M. S. van Praag, of members of the Dutch Consumer Union. Their willingness to make available the data for the study is gratefully acknowledged. We thank Floor van Herwaarden, Bernard van Praag, Roberto Wessels, and the referees for their helpful suggestions with respect to an earlier version. The research reported is part of the Leyden Income Evaluation Project. I Throughout the paper the term utility function will be used to denote the general concept, whereas the term welfare function will be used for the more narrowly defined concept introduced in section II. 2 In any case one has to specify functional forms for the demand equations. Even when using flexible forms (e.g., Christensen, Jorgenson, and Lau, 1975) the specification may be expected to affect the result. 3 For example, it is usually assumed that individuals have identical functions, or that an individual's parameters are not affected by consumption patterns of other individuals, that functions do not shift over time, etc. Moreover, estimation is often based on aggregate data. 4 The empirical investigations in the present paper are concerned with durables. Extrapolating Koo's findings we would expect HM to be violated relatively often for these expenditure categories, since durables are bought infrequently.